THE FUNCTION OF INDONESIAN LANGUAGE AS A MASS MEDIA - Diah Kusyani; Satriadi; Pasaribu, Gumarpi Rahis (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2024)
"The aim of this research is to determine the "Function of Indonesian as Language Mass Media" and increase the researcher's knowledge. This research is also motivated by the fact that mass media has a very strategic role in the development and development of the Indonesian language. The strategic role of mass media is in line with the development of information technology as a very important need for humans. Current and factual information about various events and ideas about humanity's future can be quickly and easily obtained from various mass media. Therefore, apart from being a modern information medium, mass media also plays a very important role as a means of developing and fostering the Indonesian language. This research method uses descriptive qualitative research, which is carried out by describing facts from several sources. This method not only describes, but also provides understanding and the facts described are obtained using literature study techniques. Literature study is a data collection method directed at data and information seekers through various sources such as books, journals, articles, scientific and other sources that can support the writing process.”